2015
DOI: 10.1016/j.jdiacomp.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a patient’s concordant and discordant chronic conditions on diabetes care quality measures

Abstract: Aims Most patients with diabetes have comorbid chronic conditions that could support (concordant) or compete with (discordant) diabetes care. We sought to determine the impact of the number of concordant and discordant chronic conditions on diabetes care quality. Methods Logistic regression analysis of electronic health record data from 7 health systems on 24,430 patients with diabetes aged 18-75 years. Diabetes testing and control quality care goals were the outcome variables. The number of diabetes-concord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 29 publications
5
56
0
Order By: Relevance
“…; Healthcare Cost and Utilization Project ; Magnan et al. ). Each patient's concordant chronic conditions were identified by ICD‐9‐CM codes billed at one or more clinical encounters during the baseline year.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…; Healthcare Cost and Utilization Project ; Magnan et al. ). Each patient's concordant chronic conditions were identified by ICD‐9‐CM codes billed at one or more clinical encounters during the baseline year.…”
Section: Methodsmentioning
confidence: 99%
“…including a patient's specific comorbidities, socioeconomic factors, insurance status, health beliefs, and other patient contextual factors (Bayliss et al 2014). The role of comorbidities in diabetes care cannot be overlooked as over 80 percent of patients with diabetes have multiple chronic conditions (diabetes plus at least one comorbid condition) (Bae and Rosenthal 2008;Magnan et al 2015c). Conceptual and early analytic studies have suggested that patients' comorbid conditions can alter their care quality and morbidity, even after controlling for patient demographics and health care utilization (Piette and Kerr 2006;Lee et al 2007;Magnan et al 2015d).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…If pain management with NSAIDs is prioritized over reducing risk of CKD progression, patients may be at increased risk of acute kidney injury or worsening hypertension . The presence of concordant conditions may increase the likelihood of achieving chronic disease management goals as has been shown in diabetes . In contrast, having co‐occurring discordant/unrelated conditions may also complicate chronic disease self‐management or meeting quality of care goals .…”
Section: Discussionmentioning
confidence: 99%